Antepartum Hemorrhage in Obstetrics Is Still a Maternal/Fetal Killer - Shaikh, Fozia; Soomros, Shabana Bano; Shaikh, Aurangzeb; Memon, Mehwish; Memon, Mehak; Ali, Majida (Biological and Clinical Sciences Research Journal, 2025)
Antepartum hemorrhage (APH), defined as bleeding from the genital tract after 20 weeks of gestation but before the birth of the baby, remains a significant cause of maternal and perinatal morbidity and mortality, especially in low-resource settings. Early identification and prevention strategies are crucial for improving outcomes. Objective: To determine the frequency and associated risk factors of antepartum hemorrhage among women who delivered between January 2020 and December 2024 at a tertiary care hospital in Larkana, Pakistan. Methods: This retrospective descriptive study was conducted at the Gynecological Unit of Shaikh Zayad Women's Hospital, affiliated with Shah Abdul Latif University, Khairpur. Data from 672 pregnant women aged 21 to 49 years who presented with antepartum hemorrhage were included. The study population included both primigravida and multigravida women at preterm (20–36+6 weeks) and term (37–42 weeks) gestation. Continuous variables were expressed as mean ± standard deviation (SD), and categorical variables were presented as frequencies and percentages. The chi-square test was employed to evaluate categorical associations, while independent t-tests compared continuous variables between anemic and non-anemic women with APH. A p-value < 0.05 was considered statistically significant. Data analysis was conducted using SPSS version 20. Results: Results showed that women aged 33–47 years had significantly higher odds of experiencing APH compared to those aged 16–32 years (p < 0.05). A previous history of abortion was associated with a twofold increase in APH risk, while women with a history of cesarean section had a 5.7 times higher likelihood of developing APH compared to those without such a history. Additional associated factors included anemia, multiparity, malnutrition, and previous episodes of APH. Conclusion: This study highlights key risk factors for antepartum hemorrhage, including advanced maternal age, multiparity, anemia, malnutrition, prior abortion, previous cesarean delivery, and history of APH. Public health efforts should focus on reducing preventable risk factors such as unnecessary cesarean sections and unsafe abortions while improving antenatal care to mitigate APH-related complications.